Definition of occult hypoperfusion in trauma: A systematic literature review. Issue 3 (March 2023) - Shehu, A.; Kalbas, Y.; Teuben, M.P.J.; Pape, H.C.; Pfeifer, R.
Highlights: · Definitions for occult hypoperfusion in trauma (tOH) differ markedly in the literature. · The described impact of tOH on outcome differs between studies, and it´s role in trauma remains unclear. · A systematic review was performed to identify utilized criteria for tOH in recent literature. · The following definition for tOH is proposed: Lactate > 2 mmol/l or BE 〈-3 mmol/l plus SBP 〉 90 mmHg and PR < 120 bpm. Abstract: Introduction: Occult hypoperfusion (OH) entails inadequate tissue oxygenation in the presence of normal vital signs. Numerous studies have demonstrated that this phenomenon is associated with impaired outcome and increased mortality, however definitions of OH differ between studies. The aim of the current study was to identify and evaluate the published definitions of the term `occult hypoperfusion` in trauma (tOH). Material & methods: A review of literature was performed using the Medline database. The following MeSH terms have been used: occult hypoperfusion, severe trauma, polytrauma, resuscitation. Clinical studies on OH were included and utilized definitions have been compared. A predefined data-interpretation process was applied to create an integrative definition for tOH. Results: A total of 43 publications used the term OH. A definition of OH was provided in 16 manuscripts. A pooled mean number of participants of 729 (SD: 1158) was found per study. The majority of manuscripts combine multiple parameters for inadequate tissue oxygenation and normal vital signs to define OH in trauma. In 12 manuscripts, specific cut-off values for hemodynamic parameters (SBP/PR/UP) and in 11/16 papers exact metabolic thresholds (lactate/B.E) were defined. The following definition best integrates definitions in current literature: Lactate > 2 mmol/l or BE <-3 mmol/l (to define inadequate oxygenation) plus SBP > 90 mmHg and PR < 120 bpm (to define normal macroperfusion). Conclusions: The current systematic review demonstrates that definitions of occult hypoperfusion in trauma differ in the literature. The following comprehensive definition for (tOH) is proposed: Lactate > 2 mmol/l or BE <-3 mmol/l plus SBP > 90 mmHg and PR < 120 bpm. This recommendation appears to represent current literature on tOH and may improve the identification of trauma patients at risk for OH and related complicated courses. Further validation studies are required to demonstrate the clinical role of tOH and the proposed definition.